The importance of pedagogical internships for promoting social values among future teachers of preschool education - Kharkivska, A.; Molchaniuk О. (Problems of Engineer-Pedagogical Education, 2021)
The research is devoted to the importance of pedagogical internships for future specialists in the field of preschool education. The author determined that pedagogical internships provide generalization and systematization of theoretical knowledge acquired in higher education institutions, acquisition of practical skills necessary to perform professional duties well, development of pedagogical thinking, professional abilities, harmonious personality development in general, and offer an opportunity to carry out other educational tasks. The paper substantiates that the purpose of doing an internship is to master modern technologies, methods and techniques of the chosen profession, and to learn relevant skills and abilities. The objectives of pedagogical internships include developing creative abilities and an individual pedagogical style, studying advanced pedagogical experience, developing values and spiritual culture of every individual. It was found that to solve the problems faced by higher education seekers, it is necessary to take into account certain approaches (axiological, systemic, acmeological, activity-based, personal) of the educational process, and upbringing in particular. The analysis of the scientific and pedagogical literature showed that the axological approach involves taking into account the values of each person and society as a whole; the systemic approach means perceiving all objects of the educational process as a single system; the acmeological approach is about constant development and self-improvement of the individual in their professional activity; the activity-based approach considers activity to be the basis of human development; the personal approach means taking into account the individuality of the human being. The article examines the role of values, including social ones, as well as the importance of the process of promoting social values among future preschool teachers. The author found that this category of values is important for the future educator, because the teaching profession is social and requires having stable beliefs and principles, as well as paying attention to the characteristics of every single child. Pedagogical internships are proved to contribute to the achievement of positive results in promoting social values among future teachers of preschool education, as the axiosphere of the personality of higher education students develops as they dive into the teaching profession and get to communicate with children.